Le droit des valeurs mobilières et le retour des compagnies publiques au statut de compagnie privée - Alain, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This article examines the « going private » phenomenon as it has developed in the United States and Canada over the past few years as well as its implications for Quebec law. « Going private » transactions involve different means of corporate reorganization that allow a few controlling shareholders to eliminate, without adequate compensation, most other shareholders from further participation in a corporate body. Such transactions are of interest to those who study company law or securities law as the methods employed often go beyond the spirit of both. The author attempts to demonstrate the role each can play in preventing abuses of minority rights. Corporate law, while ensuring majority rule, seeks to protect individual shareholders while securities law has developed to avoid the manipulation of individual shareholders in transactions involving securities. The author believes that « going private » should take place only if full disclosure of the aims of the controlling group have been given to the minority, if there is a valid business purpose for going private and if the eliminated shareholders are treated fairly. Examples of these criteria are to be found in recent American, Canadian and Quebec jurisprudence as well as in the policy statements of the Securities Exchange Commission and the Ontario Securities Commission. These are analysed in relation to present Quebec law. The author suggests that the Quebec Securities Commission should adopt a policy statement on « going private » similar to that of the OSC. This would be a better means of ensuring that the Quebec Securities Commission fulfill its role of promoting investor protection and an efficient securities market.